Cuba in the CGIAR centres : a study of their collaboration in agricultural research - Sanchez, Pedro A (World Bank Washington DCUS, 1986)
Describes the physical, historical, and political setting of Cuba. Gives overview of its economy. Reviews agricultural sector focusing on its structure, agricultural output and inputs, food production and imports, and food consumption and distribution. Examines national agricultural research system highlighting research institutions and resources. Discusses collaboration between the Cuban agricultural research system and international centres in areas of rice, beans, cassava and tropical starchy crops, tropical pastures, potatoes, maize and sorghum. Notes constraints to such collaboration. Assesses research impact on agricultural production.